Engagement as a Dynamic but Perceivable Variable in Language Classroom Interactions - Shepherd, Lydia (2022)
A Master of Arts thesis in Teaching English to Speakers of Other Languages (TESOL) by Lydia Shepherd entitled, “Engagement as a Dynamic but Perceivable Variable in Language Classroom Interactions”, submitted in May 2022. Thesis advisor is Dr. Tammy Gregersen. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).